Aqueous dispersion of halogenated vinyl polymer, multilayer film and blister packaging for pharmaceuticals
By adding specific anionic amphiphilic compounds to the aqueous dispersion of ethylene halogenated polymers, the problems of coating properties and molding properties are solved, and uniform coating film and efficient barrier properties are achieved.
Patent Information
- Application Number
- CN202180014244.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-27
- Filing Date
- 2021-03-09
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-03-09
AI Technical Summary
The existing aqueous ethylene halogenated polymer dispersions are prone to poor leveling and orange peel patterns when repeatedly coated, and may cause film foaming during high-temperature molding, making it impossible to obtain a uniform coating film.
By mixing a specific amount of anionic amphiphilic compound with a hydrophilicity index less than 41.0 in the aqueous dispersion of ethylene halogenated polymer, the coating properties and molding properties are optimized to avoid poor leveling and foaming.
Excellent coating properties during repeated coating are achieved, poor leveling and orange peel patterns are avoided, and foaming is prevented during film forming, and a uniform coating film is obtained.
Smart Images

Figure BDA0003794681850000101 
Figure BDA0003794681850000111 
Figure BDA0003794681850000261
Abstract
Description
Technical Field
[0001] The present invention relates to aqueous dispersions of halogenated vinyl polymers, multilayer films and blister packages for pharmaceuticals. Background Art
[0002] In order to maintain the quality of food and medicine, it is necessary to block the gases such as oxygen, nitrogen, carbon dioxide and water vapor in the atmosphere and seal them. Among various resins, vinylidene chloride copolymer latex exhibits high water vapor and oxygen barrier properties when coated on the film, so it is suitable for food and medicine packaging.
[0003] In recent years, higher gas barrier properties have been required in these film applications. To solve this problem, it is effective to repeatedly apply latex to thicken the barrier layer, but when using existing latex, there are problems such as rough coating appearance and impaired transparency. Specifically, if the surface tension of the latex aqueous dispersion is not within an appropriate range, poor leveling will occur, and an orange peel pattern will be formed during repeated coating (recoating). In addition, when forming a blister package for medicines, if the molding is performed at a high temperature, foaming will occur in the film.
[0004] Various studies have been conducted in view of the above-mentioned issues.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 48-58078
[0008] Patent Document 2: Japanese Patent Application Publication No. 2000-239468
[0009] Patent Document 3: Japanese Patent Publication No. 47-29373
[0010] Patent Document 4: Japanese Patent Application Laid-Open No. 8-239536 Summary of the invention
[0011] Problems to be solved by the invention
[0012] Patent Document 1 discloses that when a vinylidene chloride copolymer latex is obtained by emulsion polymerization, sodium dodecylbenzenesulfonate is mixed in an amount of 2.5 parts by mass relative to the solid content of the resin as an amphiphilic compound. However, the amphiphilic compound here is added for the purpose of properly performing polymerization and needs to be mixed in a large amount, so foaming occurs during molding, and the recoatability is not sufficient, and the effect of the present application cannot be obtained.
[0013] Patent Document 2 discloses that a specific nonionic amphiphilic compound as a defoaming agent is contained in an amount of 0.005 to 0.12 parts by mass relative to a vinylidene chloride copolymer latex. However, since the amount added is too small, the coating properties are insufficient.
[0014] In Patent Document 3, when a polymer in which 50 wt % or more of all surfactants are anionic amphiphilic agents is overlapped on a substrate, a vinylidene chloride copolymer in which 55 wt % or more of all surfactants are nonionic amphiphilic substances is overlapped, but its water content and crystallinity are insufficient, so foaming occurs during molding, and the effect of the present application cannot be obtained.
[0015] Patent Document 4 describes an example in which a hydroxyl-containing radical polymerizable monomer and sodium dodecyl sulfonate are used. However, the water content is insufficient, so foaming occurs during molding, and the effect of the present application cannot be obtained.
[0016] Therefore, an object of the present invention is to provide an aqueous dispersion which has excellent coating properties when repeatedly coated, does not cause poor leveling and orange peel patterns, and does not cause foaming during film formation, thereby providing a uniform coating film.
[0017] Means for solving problems
[0018] The present invention has repeatedly conducted intensive studies to solve the above-mentioned problems and has found that by mixing a specific amount of a specific amphiphilic compound into an aqueous dispersion of a halogenated vinyl polymer, excellent coating properties can be achieved during repeated coating without causing poor leveling, orange peel patterns, or foaming, and a uniform coating film can be obtained.
[0019] That is, the present invention is as follows. [1]
[0021] An aqueous dispersion of a vinyl halide polymer, characterized in that it contains the vinyl halide polymer and contains more than 0 mass % and less than 2.5 mass % of an anionic amphiphilic compound having a hydrophilicity index less than 41.0 relative to the resin solid content. [2]
[0023] An aqueous dispersion of a vinyl halide polymer as described in [1], comprising sodium pyrophosphate. [3]
[0025] The aqueous dispersion of the vinyl halide polymer as described in [1] or [2] contains more than 0.12 mass % of a nonionic amphiphilic compound based on the resin solid content. [4]
[0027] A multilayer film characterized by comprising a layer obtained by applying the aqueous dispersion of the vinyl halide polymer described in any one of [1] to [3] to a base film composed of a polymer different from the vinyl halide polymer. [5]
[0029] The multilayer film as described in [4] has two or more layers coated with the aqueous dispersion of the halogenated vinyl polymer. [6]
[0031] The multilayer film as described in [4] or [5], wherein at least one of the layers coated with the aqueous dispersion of the vinyl halide polymer has a thickness of 1 μm or more. [7]
[0033] The multilayer film according to any one of [4] to [6], wherein at least one of the layers coated with the aqueous dispersion of the vinyl halide polymer has a thickness of 30 μm or more. [8]
[0035] The multilayer film according to any one of [4] to [7], wherein the water content is 1% by mass or less. [9]
[0037] The multilayer film according to any one of [4] to [8], wherein the layer coated with the aqueous dispersion of the vinyl halide polymer has a relative crystallinity of 1.1 or more as measured by a Fourier transform infrared spectrophotometer.
[10]
[0039] A blister package for medicines, characterized in that it comprises the multilayer film described in any one of [4] to [9].
[0040] Effects of the Invention
[0041] Since the aqueous dispersion of the vinyl halide polymer of the present invention has the above-mentioned constitution, it has excellent coating properties during repeated coating, does not cause poor leveling and orange peel patterns, and does not cause foaming during film formation, thereby forming a uniform coating film. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 : (a) is an evaluation standard of coating property. (b) is an evaluation of △, and (c) is an evaluation of ×.
[0043] Figure 2 : (a) is an evaluation standard of recoatability. (b) is an evaluation of △, and (c) is an evaluation of ×. DETAILED DESCRIPTION
[0044] The specific implementation mode of the present invention (hereinafter referred to as "this implementation mode") is described in detail below. The following implementation mode is an example for explaining the present invention and is not intended to limit the present invention to the following content. The present invention can be implemented by appropriately deforming within the scope of its main points.
[0045] [Aqueous dispersion of vinyl halide polymer]
[0046] The aqueous dispersion of the halogenated vinyl polymer of the present embodiment contains the halogenated vinyl polymer and contains more than 0% by mass and less than 2.5% by mass of anionic amphiphilic compounds having a hydrophilicity index of less than 41.0 relative to 100% by mass of the resin solid content. As a result, the coating property during repeated coating is excellent, poor leveling and orange peel patterns are not easily generated, and no foaming occurs during film molding, so that a uniform coating film can be obtained.
[0047] The aqueous dispersion of the vinyl halide polymer according to the present embodiment may further contain more than 0.12% by mass of a nonionic amphiphilic compound based on 100% by mass of the resin solid content.
[0048] The aqueous dispersion of the vinyl halide polymer is preferably obtained by emulsion polymerization of monomers containing at least vinyl halide.
[0049] It should be noted that in this specification, the aqueous dispersion of halogenated vinyl polymer is sometimes referred to as aqueous dispersion. In addition, the resin solid content in the aqueous dispersion of the present embodiment refers to the total amount of all solid resins contained in the aqueous dispersion, which may be only halogenated vinyl polymer or may contain other resin components.
[0050] (Halogenated vinyl polymers)
[0051] The vinyl halide polymer contains at least a structural unit derived from vinyl halide, and may further contain a monomer copolymerizable with vinyl halide.
[0052] In addition, in this specification, the monomer copolymerizable with the vinyl halide may be referred to as a comonomer.
[0053] Examples of the vinyl halide include compounds having a structure in which one or more hydrogen atoms of the vinyl group are replaced by halogen atoms, for example, compounds in which one or more hydrogen atoms of the vinyl group are replaced by halogen atoms. Examples of the halogen atoms include fluorine, chlorine and bromine.
[0054] Examples of the vinyl halides include chlorine monomers such as vinyl chloride, vinylidene chloride, 1,2-dichloroethylene, trichloroethylene, and tetrachloroethylene; fluorine monomers such as vinyl fluoride, vinylidene fluoride, trifluoroethylene, and tetrafluoroethylene; and bromide monomers such as vinyl bromide, vinylidene bromide, tribromoethylene, and tetrabromoethylene. One or more of the vinyl halides can be selected for use. Among these, chlorine monomers are preferred from the perspective of ease of polymerization, and vinylidene chloride is particularly preferred from the perspective of barrier function.
[0055] As monomers copolymerizable with halogenated vinyl, for example, acrylates such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, methacrylates such as methyl methacrylate, glycidyl methacrylate, nitriles such as acrylonitrile and methacrylonitrile, and unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, and maleic acid can be cited. One or more of the above-mentioned comonomers can be selected for use. Among them, acrylates, methacrylates, methacrylonitrile, acrylonitrile, and acrylic acid are preferred, and methyl acrylate, methyl methacrylate, methacrylonitrile, and acrylic acid are more preferred. From the aspect of the softness of the coating film, methyl acrylate and acrylic acid are also particularly preferred.
[0056] The above-mentioned halogenated vinyl polymer is preferably a copolymer containing 50% by mass or more of a structural unit derived from a halogenated vinyl (e.g., a halogenated vinyl) relative to 100% by mass of the halogenated vinyl polymer. By making the mass ratio of the structural unit derived from the halogenated vinyl (e.g., a halogenated vinyl) within this range, the barrier property and film-forming property are excellent. The above-mentioned mass ratio is more preferably 60% by mass or more, further preferably 70% by mass or more, further preferably 80% by mass or more, further preferably 85% by mass or more, and particularly preferably 90% by mass or more. In addition, from the aspect of showing good film-forming properties, it is preferably 99% by mass or less, more preferably 96% by mass or less, and particularly preferably 94% by mass or less.
[0057] The mass ratio of the ethylene halide polymer in the aqueous dispersion of the present embodiment preferably contains 20 mass % or more of the ethylene halide polymer in terms of solid content from the perspective of coating properties, and more preferably 30 mass % or more, further preferably 40 mass % or more, further preferably 50 mass % or more, and particularly preferably 55 mass % or more from the perspective of better coating properties. In addition, it is preferably 90 mass % or less, more preferably 80 mass % or less, further preferably 70 mass % or less, and particularly preferably 65 mass % or less.
[0058] The mass ratio of the halogenated vinyl polymer refers to the value measured by the loss on drying method, and is measured by the following method: 2 to 4 g of an aqueous dispersion (e.g., latex) is dropped onto a glass fiber mat using a dropper using a SMART System 5 manufactured by CEM, and the solid content (mass %) is calculated by multiplying the dry mass / mass of the aqueous dispersion by 100 after the output is 40% raised in temperature.
[0059] The vinyl halide polymer in the aqueous dispersion of the present embodiment is preferably in a particle form.
[0060] From the aspect of excellent surface smoothness when coated into a film, the average particle size of the above-mentioned vinyl halide polymer is preferably 50 nm or more, more preferably 75 nm or more, further preferably 100 nm or more, and particularly preferably 125 nm or more. In addition, from the aspect of obtaining a good film, it is preferably 300 nm or less, more preferably 250 nm or less, and further preferably 200 nm or less.
[0061] The average particle size is a value measured by a dynamic light scattering method and is measured by the following method: 5 to 9 cc of an aqueous dispersion of a vinyl halide polymer diluted 100 times with pure water is dispensed into a glass measuring cell (Cent Tube STS-2 manufactured by Maruemu) using FPAR-1000 manufactured by Otsuka Electronics and measured by a dynamic light scattering method.
[0062] (Anionic amphiphilic compounds)
[0063] The above-mentioned anionic amphiphilic compound is an amphiphilic compound that ionizes when dissolved in water and shows anionicity. In this specification, anionicity refers to an amphiphilic agent whose hydrophilic group part measured by H-NMR is ionized into negative ions in water. In addition, nonionic refers to an amphiphilic agent having a hydroxyl group or ether bond in which ions do not dissociate in water in the structure measured by H-NMR.
[0064] The hydrophilicity index of the anionic amphiphilic compound is less than 41.0.
[0065] By making the hydrophilicity index small, the amphiphilic compound shows moderate hydrophobicity. Thus, the surface of the halogenated vinyl polymer (e.g., particle surface) is modified, and the compatibility with the halogenated vinyl polymer is good when drying. Therefore, it will enter the particles when drying, and will not seep out to the surface to form a coating film. As a result, it is not easy to produce uneven surface tension, and it is not easy to produce poor leveling when repeatedly coated. In addition, since the water retention is small, the evaporation of water in the film can be promoted when drying, and the water content of the coating film after film formation can be reduced, so the foaming during film molding can be suppressed. The lower the hydrophilicity index, the easier it is to obtain the above effect, preferably below 38.0, more preferably below 34.0. The lower limit is not particularly set, and considering the water solubility of the amphiphilic compound and the affinity with the halogenated vinyl polymer, it is preferably above 1.0, more preferably above 5.0, further preferably above 10.0, and particularly preferably above 20.0.
[0066] The above-mentioned hydrophilicity index can be calculated by the following method.
[0067] Hydrophilicity index = (molecular weight of hydrophilic groups in the chemical structure of the amphiphilic compound containing salts that ionize in water) / (molecular weight of the amphiphilic compound containing salts that ionize in water) × 100
[0068] In addition, the molecular weight is calculated by calculation based on the constituent atoms of the substance identified by the measurement based on H-NMR described later.
[0069] The hydrophilic group mentioned here is an atomic group that forms a weak bond with water molecules through electrostatic interaction, hydrogen bonding, etc. and is stable in water. The types of the above-mentioned hydrophilic groups are not particularly limited, and hydroxyl, carboxyl, sulfo, sulfate, sulfonic acid, phosphoric acid, sulfosuccinic acid, amino acid, monosaccharide, disaccharide, polysaccharide, glycerol, etc. can be cited, which are bonded to the hydrophobic group through ester bonds, ether bonds, etc. In these hydrophilic groups, a part of the hydrogen in the structure is replaced by salts of alkali metals such as potassium, sodium, and calcium or alkaline earth metals.
[0070] When the aqueous dispersion contains two or more anionic amphiphilic compounds, the hydrophilicity index uses a value obtained by calculating the value of each component alone using the above formula and averaging the values according to their mass ratio.
[0071] The mass ratio of the anionic amphiphilic compound in the aqueous dispersion of the present embodiment is greater than 0 mass % and less than 2.5 mass % relative to 100 mass % of the resin solid content contained in the aqueous dispersion, from the viewpoint of excellent recoatability when the aqueous dispersion is coated with a film and suppression of foaming during drying, preferably 2.0 mass % or less, more preferably 1.5 mass % or less, further preferably 1.0 mass % or less, and particularly preferably 0.7 mass % or less, from the viewpoint of obtaining good coating properties. In addition, the mass ratio is preferably 0.05 mass % or more, more preferably 0.1 mass % or more, further preferably 0.2 mass % or more, particularly preferably 0.3 mass % or more, and very preferably 0.4 mass % or more.
[0072] Examples of the anionic amphiphilic compound include carboxylates, sulfate ester salts, sulfonates, phosphate ester salts, and gemini amphiphilic compounds.
[0073] The carboxylates include soaps, and the ingredients classified as soaps include sodium caprylate, sodium caprate, sodium laurate, sodium myristate, sodium palmitate, sodium stearate, sodium oleate, sodium perfluorooctanoate, sodium N-lauroyl sarcosinate, sodium cocoyl glutamate, and α-sulfo fatty acid methyl ester salts.
[0074] The components classified as the above-mentioned sulfate ester salts include higher alcohol sulfate ester salts, higher alkyl ether sulfate ester salts, sulfated oils, sulfated fatty acid esters and sulfated fatty acids, and compounds obtained by sulfated higher alcohols having alkyl groups can be used. Higher alcohol sulfate ester salts include sodium dodecyl sulfate, sodium myristyl sulfate, sodium hexadecyl sulfate, sodium stearyl sulfate, sodium oleyl sulfate, etc. Higher alkyl ether sulfate ester salts are a general term for sulfate ester salts made by adding ethylene oxide to higher alcohols. Amphiphilic compounds used by sulfated them include sodium lauryl ether sulfate, sodium myristyl ether sulfate, sodium hexadecyl ether sulfate, sodium stearyl ether sulfate, sodium oleyl ether sulfate, secondary alcohol ethylene oxide adduct sulfate, etc. Sulfated oils, sulfated fatty acid esters and sulfated fatty acids are general terms for anionic amphiphilic compounds made by sulfated fatty acids or fatty acid esters having hydroxyl groups or double bonds. Sulfated oils are a general term for substances obtained by sulfating and neutralizing waxes esterified with higher aliphatic alcohols of higher fatty acids, and examples thereof include Turkish red oil obtained by sulfating castor oil, sulfated olive oil, sulfated beef tallow, sulfated peanut oil, sulfated sperm whale oil, and esters thereof.
[0075] Sulfonate is generally a general term for components having a structure represented by R-SO3Na, and includes, for example, sodium 1-hexanesulfonate, sodium 1-octanesulfonate, sodium 1-decanesulfonate, sodium 1-dodecanesulfonate, sodium perfluorobutanesulfonate, sodium linear alkylbenzenesulfonate, sodium naphthalenesulfonate, sodium naphthalenedisulfonate, sodium naphthalenetrisulfonate, sodium butylnaphthalenesulfonate, sodium perfluorooctanesulfonate, etc. It should be noted that sodium linear alkylbenzenesulfonate includes sodium toluenesulfonate, sodium cumenesulfonate, sodium octylbenzenesulfonate, and sodium dodecylbenzenesulfonate.
[0076] Examples of the phosphoric acid ester salt include lauryl phosphoric acid, sodium lauryl phosphate, potassium lauryl phosphate, etc. Phosphoric acid ester salts include those obtained by adding ethylene oxide to these substances.
[0077] The gemini amphiphilic compound is a compound having two fatty acid chains in one molecule, and examples thereof include dialkyl sulfosuccinate salts.
[0078] The anionic amphiphilic compound may be used alone or in combination of two or more as long as it satisfies the above-mentioned range of the hydrophilicity index.
[0079] Preferred anionic amphiphilic compounds include soaps, sulfonates, and gemini compounds. More preferred examples include sodium alkylbenzenesulfonates such as sodium dodecylbenzenesulfonate, sodium alkylsulfonates, sodium palmitate, and dialkylsulfosuccinates. Further preferred examples include sodium dodecylbenzenesulfonate and dialkylsulfosuccinates, and particularly preferred is sodium dodecylbenzenesulfonate.
[0080] (Non-ionic amphiphilic compound)
[0081] The nonionic amphiphilic compound that can be used in the aqueous dispersion of the present embodiment is an amphiphilic compound having a hydrophilic group such as a hydroxyl group or an ether bond (polyoxyethylene chain or the like) that does not undergo ion dissociation in water.
[0082] Examples of the nonionic amphiphilic compound include ester type, ether type, ester ether type, alkanolamide type, alkyl glycoside, and higher alcohol.
[0083] Examples of the ester type include lauric acid glyceryl, monostearate glyceryl, sorbitan fatty acid ester, and sucrose fatty acid ester.
[0084] Examples of the ether type include pentaethylene glycol monododecyl ether and octaethylene glycol monododecyl ether, which are polyoxyethylene alkyl ethers.
[0085] Examples of the ester ether type include polyoxyethylene glycerol fatty acid esters, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene sorbitol fatty acid esters, sorbitan fatty acid ester polyethylene hexitan fatty acid esters, and sorbitan fatty acid ester polyethylene glycol.
[0086] Examples of the alkanolamide type include lauric acid diethanolamide, oleic acid diethanolamide, stearic acid diethanolamide, and coconut oil fatty acid diethanolamide.
[0087] Examples of the alkyl glycoside include octyl glucoside, decyl glucoside, and lauryl glucoside.
[0088] Examples of the higher alcohol include cetyl alcohol, stearyl alcohol, and oleyl alcohol.
[0089] The nonionic amphiphilic compound may be used alone or in combination of two or more.
[0090] As the nonionic amphiphilic compound, polyoxyethylene alkyl ether ammonium sulfate, polyoxyalkylene decyl ether, and polyoxyethylene oleyl ether are preferred.
[0091] The lower the critical micelle concentration (also referred to as CMC) of the nonionic amphiphilic compound, the better the recoatability, and thus it is preferred. The above critical micelle concentration is preferably 0.15 mass % or less, more preferably 0.10 mass % or less, and further preferably 0.06 mass % or less. In addition, considering the water solubility of the amphiphilic compound and the affinity with the halogenated vinyl polymer, it is preferably 0.001 mass % or more, more preferably 0.005 mass % or more, further preferably 0.01 mass % or more, and particularly preferably 0.03 mass % or more.
[0092] Critical micelle concentration can be measured by the following method. First, the amphiphilic compound is dissolved in water at a concentration of 0.001 mass%, 0.005 mass%, 0.010 mass%, 0.015 mass%, 0.020 mass%, 0.025 mass%, 0.030 mass%, 0.035 mass%, 0.040 mass%, 0.045 mass%, 0.050 mass%, 0.055 mass%, 0.060 mass%, 0.065 mass%, 0.070 mass%, 0.075 mass%, 0.080 mass%, 0.085 mass%, 0.090 mass%, 0.095 mass%, 0.1 mass% to make an aqueous solution, and the surface tension is measured by the Wilhelmy method respectively. In the determination of surface tension, an automatic surface tensiometer CBVP-Z (Kyowa Interface Chemical) is used to measure in a constant temperature chamber at 20°C and 55%RH. The obtained surface tension was plotted for each concentration (mass %). As the concentration increased from the low concentration side, the surface tension decreased, but the value became constant after a certain concentration. The concentration (mass %) at the inflection point was taken as the critical micelle concentration.
[0093] When the aqueous dispersion contains a plurality of nonionic amphiphilic compounds, the critical micelle concentration is determined by the above method for each component single substance of the nonionic amphiphilic compound, and the average value is used based on their mass ratio.
[0094] The mass ratio of the nonionic amphiphilic compound is preferably greater than 0.12 mass %, more preferably 0.15 mass %, more preferably 0.2 mass %, more preferably 0.3 mass %, and particularly preferably 0.5 mass % or more, based on 100 mass % of the resin solid content in the aqueous dispersion of the halogenated vinyl polymer, from the aspect of coating properties during film coating. In addition, from the aspect of obtaining good coating properties, it is preferably 1.5 mass % or less, and more preferably 1.0 mass % or less.
[0095] The qualitative and quantitative analysis of the anionic amphiphilic compound and / or the nonionic amphiphilic compound is performed by the following method, and either H-NMR or LC / MS can be used.
[0096] <Analysis by H-NMR>
[0097] (A) Take 10 ml of latex and freeze-dry it. Confirm that the residual amount of solvent is less than 0.1% by mass of the total mass. Dissolve 0.5 g of the obtained freeze-dried product in 10 ml of tetrahydrofuran. (B) Add 40 ml of methanol to the above tetrahydrofuran solution for reprecipitation. Then filter the liquid to remove the precipitate. Use the filtrate to concentrate it to dryness using an evaporator. (C) Add 5 ml of a solvent of tetrahydrofuran / methanol in a ratio of 1 to 1 (volume ratio) to the concentrated dry product and dissolve it. (D) After air-drying 1 ml of the obtained solution, dissolve it in a solvent of deuterated tetrahydrofuran / deuterated methanol in a ratio of 1 to 1, and add 10 μl of maleic acid as an internal standard substance to the obtained sample. The sample is measured by H-NMR under the following conditions for qualitative and quantitative analysis.
[0098] H-NMR measurement conditions
[0099] (Device) ECS400 manufactured by JEOL Resonance
[0100] (Observation core (observation frequency)): 1H (399.78MHz)
[0101] (Pulse program): Single pulse (1H)
[0102] (Integral times): 256 times (1H) 18000 times (13C)
[0103] (Lock solvent): THF-d8
[0104] (Chemical shift standard): THF (1H: 1.80ppm 13C: 67.38ppm)
[0105] <Analysis by LC / MS>
[0106] The concentrated dry solid obtained after the pretreatment of (B) was carried out in the same manner as in the above-mentioned <Analysis by H-NMR>, and was diluted 20 to 100 times by adding methanol, and then measured by LC / MS.
[0107] LC / MS conditions
[0108] (Device) UPLC type manufactured by Waters, / MS Synapt G2 type manufactured by Waters
[0109] (Column used): Candenza CD-C18HT (2 mm I.D. × 30 mm) manufactured by Imtakt
[0110] (Column temperature): 40°C
[0111] (Detection): PDA 200~400nm
[0112] (Flow rate): 0.3ml / min
[0113] (Mobile phase): A = 10 mM ammonium acetate aqueous solution, B = acetonitrile
[0114] (gradient):
[0115]
[0116] Injection volume: 2μl
[0117] Ionization: ESI+, ESI-
[0118] Scan range: m / z 50~1200
[0119] The characteristic m / z are shown below.
[0120] [Table 1]
[0121]
[0122] Use 3 or more standard reagents of amphiphilic compounds with known concentrations to be detected after qualitative analysis, measure under the same conditions, and create a calibration curve based on the peak area of the characteristic m / z mass spectrum of the target component. Use the calibration curve to quantify the emulsifier concentration in the sample solution. In the case of unknown samples, use the characteristic m / z found in each amphiphilic compound as a reference for qualitative analysis.
[0123] (Sodium pyrophosphate)
[0124] The aqueous dispersion of the halogenated vinyl polymer of the present embodiment may further contain sodium pyrophosphate. The sodium pyrophosphate is a compound represented by the chemical formula Na4P2O7.
[0125] When sodium pyrophosphate is added, the viscosity of the aqueous dispersion of the halogenated polymer is reduced. This improves the leveling property during coating. In particular, the occurrence of ribbed patterns that are a cause of poor appearance caused by roller coaters, bar coaters, etc. can be prevented.
[0126] The mass ratio of the sodium pyrophosphate is preferably 0.05 mass % or more, more preferably 0.1 mass % or more, further preferably 0.18 mass % or more, and most preferably 0.25 mass % or more relative to 100 mass % of the resin solid content in the aqueous dispersion of the halogenated vinyl polymer. In addition, the upper limit is preferably 10 mass % or less, more preferably 5 mass % or less, and further preferably 3 mass % or less. By making the mass ratio 0.05 mass % or more, the effect of reducing the viscosity can be obtained, and the effect of preventing the occurrence of poor appearance such as rib patterns can be obtained.
[0127] The solvent of the aqueous dispersion of the present embodiment may be water only, or may include water and other solvents (e.g., 2,2,4-trimethylpentanediol, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether acetate, diethylene glycol diethyl ether, ethylene glycol mono-2-ethylhexyl ether, dibutyl phthalate, dioctyl phthalate, propylene glycol n-butyl ether, dipropylene glycol n-butyl ether, tripropylene glycol n-butyl ether, dipropylene glycol methyl ether, tripropylene glycol methyl ether, methanol and other film-forming aids, etc.). When other solvents are included, the amount is preferably 20 parts by mass or less relative to 100 parts by mass of the resin solid content.
[0128] In 100% by mass of the aqueous dispersion of the present embodiment, the mass ratio of the resin solid content contained in the aqueous dispersion is preferably 20% by mass or more, more preferably 40% by mass or more, and further preferably 50% by mass or more.
[0129] The mass ratio of the vinyl halide polymer relative to 100 mass % of the resin solid content contained in the aqueous dispersion is preferably 60 mass % or more, more preferably 85 mass % or more, and even more preferably 100 mass %.
[0130] (characteristic)
[0131] The characteristics of the aqueous dispersion of the vinyl halide polymer according to the present embodiment will be described below.
[0132] The surface tension of the aqueous dispersion of the present embodiment is preferably 30 mN / m or more, more preferably 40 mN / m or more, and further preferably 45 mN / m or more. The surface tension can be measured by a plate method in a constant temperature room at 20°C and 55% RH using an automatic surface tensiometer CBVP-Z (manufactured by Kyowa Interface Chemicals).
[0133] When the surface tension is within the above range, the coating can be evenly applied to the surface of the base film or the surface of the anchor coating on the base film, so that the coating is densely formed, so that defects are not likely to occur at the interface and barrier properties can be exerted. In addition, foaming is not likely to occur even during high-temperature molding.
[0134] Here, poor film formation is described.
[0135] Rib pattern refers to the periodic ridge-like (vertical stripes / rib-like) surface defects formed on the coating surface along the direction of the base film movement. Poor leveling refers to the phenomenon that the coating film is not smooth and the unevenness of the coating film generated during coating still remains. Orange peel refers to the surface unevenness or wavy pattern of the coating film after coating and drying, which is similar to the skin of citrus fruits (oranges, etc.).
[0136] Foaming during film forming is a phenomenon in which the remaining water carried into the coating film after drying is vaporized from the inside of the coating film during forming, resulting in foaming and causing poor appearance after forming. There is no particular limitation on the forming method, and examples include vacuum forming, air pressure forming, press forming, etc. Existing aqueous dispersions of halogenated vinyl polymers are prone to poor appearance when repeatedly coated for forming. For example, when using a resin solid content of 40 g / m 2 When the film is coated with a thickness of 0.5-1.00°C or more and the obtained film is molded at 130°C or more, poor appearance is likely to occur. The layer coated with the aqueous dispersion of the present embodiment is not likely to cause foaming and poor appearance, so that even when press molding is performed at 100-140°C or vacuum molding is performed at 140-180°C, a molded product (e.g., a blister package) with good appearance can be obtained.
[0137] [Multilayer film]
[0138] The multilayer film of the present embodiment has a layer formed by coating the aqueous dispersion of the vinyl halide polymer of the present embodiment on a base film. The base film is preferably a multilayer film composed of a polymer different from the vinyl halide polymer contained in the aqueous dispersion layer.
[0139] In addition, in this specification, the layer coated with the aqueous dispersion of the vinyl halide polymer of this embodiment may be referred to as an aqueous dispersion layer.
[0140] (Basement membrane)
[0141] Examples of the base film include films made of polyvinyl chloride, polyester, polyamide, and polypropylene. Polyvinyl chloride films are generally used. The thickness of the base film (sometimes referred to as substrate in this specification) varies depending on the base film used, but is generally 8 to 300 μm.
[0142] The multilayer film is not limited to being composed of the aqueous dispersion layer alone, and may be used in combination (eg, by lamination) with an aqueous dispersion layer and a copolymer layer mainly composed of a highly polymerizable monomer other than a halogenated polymer and having adjusted functionality.
[0143] When the aqueous dispersion of the halogenated vinyl polymer of this embodiment is applied to the base film constituting the above-mentioned multilayer film, the aqueous dispersion can be directly applied to the base film to form the aqueous dispersion layer, but in order to improve the adhesion between the base film and the aqueous dispersion layer, it is preferred to activate the surface of the base film before coating.
[0144] Methods for activating the surface of the base film include methods of introducing hydrophilic components such as hydroxyl groups, carboxyl groups, ester groups, ether bonds, amino groups, imino groups, amide groups, and sulfate groups onto the surface of the base film by corona discharge treatment, plasma discharge treatment, strong acid solution treatment, electron beam treatment, ultraviolet treatment, and flame treatment.
[0145] (Anchor Coating)
[0146] In the multilayer film of this embodiment, as a method for further improving the adhesion between the base film and the aqueous dispersion layer, there is a method of coating an anchor coating agent on the base film surface, drying to form an anchor coating layer, and then coating an aqueous dispersion of a vinyl halide polymer.
[0147] As the anchor coating agent applied on the surface of the base film, for example, one or more anchor coating agents selected from polyacrylic acid resins, polyurethane resins, isocyanate resins, polyester resins, oxazoline resins, and carbonimide resins can be cited, and preferably an anchor coating agent selected from polyacrylic acid resins, polyurethane resins, and isocyanate resins. The form of the anchor coating agent is not limited, and it can be any of a solution type containing an organic solvent, an aqueous solution type, and an aqueous emulsion type.
[0148] The anchor coating agent can be applied by a method commonly used in the field of film coating, such as a direct gravure method, a reverse gravure method, a gravure method, a roll coating method, a rod coating method, a doctor blade method, or an air knife method.
[0149] After coating, the coating may be dried by a known method such as hot air drying at 40° C. to 180° C., heat drying such as hot roll drying, infrared drying, or the like.
[0150] In order to maintain surface smoothness and adhesion between the base film and the anchor coating, the thickness of the anchor coating is preferably 0.1 to 2 μm. In order to improve adhesion with the base film, it is preferred to form the anchor coating after activating the base film surface and apply an aqueous dispersion of a halogenated vinyl polymer.
[0151] (Aqueous dispersion layer)
[0152] In the film of the present embodiment, the above-mentioned water dispersion layer can be provided with more than 2 layers. The water dispersion layer can be provided with more than 2 layers continuously, or it can be provided with other layers. It should be noted that in this specification, the layer formed by repeatedly applying the water dispersion of the halogenated vinyl polymer is regarded as 1 layer. Continuously providing more than 2 layers of water dispersion layers means laminating water dispersion layers with different constituent components.
[0153] The water dispersion layer is preferably provided on at least one surface of the base film by being laminated on at least a part of the surface, and more preferably provided by being laminated on the entire surface.
[0154] In the multilayer film of the present embodiment, the water dispersion layer is preferably provided on at least one surface of the base film, and more preferably provided on both surfaces.
[0155] From the perspective of barrier properties, the thickness of the water dispersion layer is preferably 3 μm or more, more preferably 10 μm or more, further preferably 20 μm or more, further preferably 30 μm or more, further preferably 50 μm or more, further preferably 60 μm or more, further preferably 70 μm or more, further preferably 90 μm or more, and particularly preferably 120 μm or more. From the perspective of film-forming properties and impact resistance, the upper limit is preferably 1000 μm or less, more preferably 800 μm or less, further preferably 500 μm or less, further preferably 300 μm or less, further preferably 200 μm or less, and particularly preferably 150 μm or less, and may be 100 μm or less, or 90 μm or less.
[0156] From the perspective of barrier properties, the dry coating thickness of the water dispersion layer is preferably 3 μm or more, more preferably 10 μm or more, further preferably 20 μm or more, further preferably 30 μm or more, further preferably 50 μm or more, further preferably 60 μm or more, further preferably 70 μm or more, further preferably 90 μm, and particularly preferably 120 μm or more. The upper limit is not particularly set, but from the perspective of film-forming properties and impact resistance, it is preferably 1000 μm or less, more preferably 800 μm or less, further preferably 500 μm or less, further preferably 300 μm or less, further preferably 200 μm or less, further preferably 150 μm or less, particularly preferably 100 μm or less, and may be 90 μm or less.
[0157] The thicker the thickness, the better the barrier property of the film to water vapor and oxygen. However, the heating of the film during bubble molding or the like becomes uneven, so foaming is likely to occur, and the bubble molded body becomes hard and it is not easy to extrude the medicine. In addition, the light yellow color becomes darker, and the appearance is impaired. The aqueous dispersion of the halogenated vinyl polymer of this embodiment contains a specific amphiphilic compound, so the above-mentioned trade-off is not likely to occur, and a film or molded body with excellent foaming, extrudability, and appearance can be obtained at a thickness that can obtain appropriate barrier properties.
[0158] The thickness of the dry coating film is measured by the following method.
[0159] The multilayer film coated with the aqueous dispersion of the present embodiment was cut using a microtome (RM2245 manufactured by LEICA) and observed using an electron microscope (TM4000plus manufactured by Hitachi) to measure the thickness of the dried coating film of the aqueous dispersion layer.
[0160] From the viewpoint of barrier properties, the weight of the dried film of the vinyl halide polymer in the aqueous dispersion layer is preferably 5 g / m 2 More preferably 40g / m 2 More preferably, 50 g / m 2 More preferably, 60 g / m 2 More preferably, 70 g / m 2 More than, particularly preferably 80g / m 2 Above, particularly preferably 90 g / m 2 From the perspective of film forming properties and impact resistance, the upper limit is preferably 1600 g / m 2 Below, more preferably 1200g / m 2 Below, more preferably 800g / m 2 Below, particularly preferably 500g / m 2 Below, particularly preferably 300g / m 2 Below, particularly preferably 160g / m 2 the following.
[0161] When the water dispersion layer has a plurality of layers, the thickness and coating quality of each layer may be the same or different.
[0162] The water content of the multilayer film of the present embodiment is preferably below 3% by mass, more preferably below 2% by mass, further preferably below 1% by mass, further preferably below 0.5% by mass, further preferably below 0.3% by mass, further preferably below 0.2% by mass, and particularly preferably below 0.1% by mass. The less the water content, the less likely it is to produce foaming when the multilayer film formed by the aqueous dispersion of the present embodiment is heated and formed, and the transparency of the film is more excellent, thus preferably. The less the water content, the more excellent the above effect, so the lower limit is not set, but as the scope of reality, it is preferably more than 0.01% by mass. The water content mentioned here is the water value measured by Karl Fischer method.
[0163] The above-mentioned water content is measured by the following method.
[0164] Using the measuring unit MKC-710M, the moisture vaporization device ADP-611, and the control unit MCU-710 manufactured by Kyoto Electronics Co., Ltd., the ADP-611 was purged with nitrogen at a flow rate of 200 ml / min for more than 30 minutes, and 0.1000 g ± 0.05 g of the multilayer film coated with the halogenated vinyl polymer was placed on the sample plate, purged at 180° C. for 3 minutes, and then measured at 160° C. The operation was repeated 3 times with the sample replaced, and the average value of the 3 times was taken as the moisture content.
[0165] In the above-mentioned water dispersion layer, the relative crystallinity (CI value) measured by Fourier transform infrared spectrophotometer (total reflection measurement method) is preferably 1.1 or more, more preferably 1.2 or more, more preferably 1.3 or more, more preferably 1.4 or more, more preferably 1.5 or more, more preferably 1.6 or more, more preferably 1.7 or more, and particularly preferably 1.8 or more. The higher the value, the higher the strength of the water dispersion layer in the multilayer film, and as a result, the water contained in the multilayer film in trace amounts is not easy to expand during heating and molding, and is not easy to grow into bubbles that can be visually confirmed, and the appearance is excellent. The higher the value, the more the above-mentioned effect can be exerted, so the upper limit is not particularly set, but as a realistic range, it is preferably below 3.0, more preferably below 2.0.
[0166] The relative crystallinity (CI value) is measured by the following method.
[0167] The IR Affinity-1S manufactured by Shimadzu Corporation was used and the resolution was set to 4 cm -1 The coated surface of vinylidene chloride was irradiated with infrared rays and measured by the ATR method.
[0168] During crystallization, it is known that chlorine enhances the CC dipole moment due to configuration change, so 1046cm -1 Taking advantage of this, the 800cm -1 Up to 1320cm -1 Connected in a straight line, through 1046cm -1 (CC bond of polyvinylidene chloride) / 1070cm -1 The ratio of the peak heights (CH bonds of the polyvinylidene chloride skeleton) was determined and this was referred to as relative crystallinity (CI value).
[0169] The method for forming the aqueous dispersion of the halogenated vinyl polymer on the above-mentioned base film can use the method usually implemented in the film coating field. As a coating method, roll coating methods such as gravure methods such as direct gravure methods, double-roller swing coating methods, bottom-feed three-roller reverse coating methods, scraper methods, air knife methods, die coating methods, rod coating methods, dipping methods, spraying methods, etc. can be applied. For the reason that the productivity is good and the aqueous dispersion layer can be easily formed, preferably gravure methods, roll coating methods, air knife methods, more preferably gravure methods are adopted. The coating amount of the aqueous dispersion during coating is different according to the thickness of the desired aqueous dispersion layer, and is not particularly limited. Can be coated and dried once or repeatedly for many times to form a desired aqueous dispersion layer, as long as it is set to a coating amount that does not cause insufficient drying or solvent residue, that is, the film properties can be effectively brought into play. In addition, the drying method is not particularly limited, and examples include a natural drying method, a drying method in an oven set to a specific temperature, a method using a dryer attached to a coater, an arch dryer, a suspension dryer, a drum dryer, an infrared dryer, etc. In addition, the drying conditions can be appropriately selected according to the drying method, for example, in the method of drying in an oven, it is preferably dried at a temperature of 60 to 200° C. for about 1 second to 5 minutes.
[0170] The above-mentioned aqueous dispersion layer may contain 0.001 to 5 parts by mass of wax relative to 100 parts by mass of the halogenated vinyl polymer. For the sake of balance between the crystallization rate and the barrier performance, it is preferably 0.005 to 3 parts by mass, and more preferably 0.01 to 1 parts by mass. The wax may contain only one kind, or may contain a wax composition consisting of two or more kinds of waxes. When containing wax (or a wax composition), it may be added to the aqueous dispersion of the halogenated vinyl polymer before forming the aqueous dispersion layer. By adding wax, the effects of improving sliding properties and preventing adhesion can be obtained. The types of the above-mentioned wax are not particularly limited, and natural or synthetic waxes may be used, for example, polyolefin wax, paraffin wax, carnauba wax, beeswax, Chinese insect wax, ozokerite and montanic acid wax, and their esters may be used alone or in the form of a composition containing them as the main component. Among them, polyolefin wax is preferably used. When wax is added to the vinylidene chloride copolymer, the initial physical properties change due to the ease of crystallization, so it is preferred to adjust the mass ratio of the wax according to the morphology of the aqueous dispersion layer in the film.
[0171] When the water dispersion layer is provided in addition to the surface layer, the water dispersion layer is preferably a layer containing no wax. When no wax is contained, the coating film cures slowly and the impact resistance of the film is good.
[0172] The multilayer film of the present embodiment can be used as a blister package, and is particularly preferably used as a blister package for medicines.
[0173] When used as a blister packaging film, a halogenated polymer having barrier properties other than those of the present invention may be used in combination.
[0174] In the multilayer film of this embodiment, a general resin film for maintaining the molded shape can be laminated between any of the base film, anchor coating layer and water dispersion layer. The laminated film is not particularly limited, and examples thereof include polyethylene, polypropylene and polyester, and the thickness is, for example, 1 to 100 μm.
[0175] (characteristic)
[0176] The characteristics of the multilayer film of this embodiment will be described below.
[0177] The oxygen permeability of the multilayer film of the present embodiment is preferably less than 2.3 cc / m2 at 23° C. and 0.1 MPa in the case of a film in which an aqueous dispersion of a vinyl halide polymer is coated on a stretched polyvinyl chloride film having a thickness of 250 μm. 2 / day.
[0178] The water vapor permeability of the multilayer film of the present embodiment is preferably less than 2.0 g / m2 at 38° C. and 100% humidity, for example, in the case of a film in which an aqueous dispersion of a vinyl halide polymer is coated on a stretched polyvinyl chloride film having a thickness of 250 μm. 2 / day.
[0179] Example
[0180] The present invention is described in more detail below by way of examples, but the present invention is not limited to the examples. In addition, in the examples and comparative examples, when simply described as parts or %, unless otherwise clearly indicated, the mass parts or mass % are indicated. It should be noted that the physical property evaluation was performed by the following method.
[0181] (Example 1)
[0182] Into a glass-lined pressure-resistant reactor, 57 parts of pure water, 0.03 parts of sodium D-arabinose ascorbate, and 0.4 parts of sodium alkyl diphenyl ether sulfonate were added when the final monomer addition amount was 100 parts, and deaeration was performed under stirring, and then the temperature of the content was maintained at 45°C. In another container, a raw material monomer mixture with a composition mass ratio of VDC / MA / AA=90.4 / 9.5 / 0.1 was prepared. 20 parts of the raw material monomer mixture were added to the above-mentioned pressure-resistant reactor at one time, and polymerization was carried out until the internal pressure decreased. Then, the remaining 80 parts of the monomer mixture were continuously and quantitatively pressed. In parallel, an initiator prepared by dissolving 0.028 parts of tert-butyl hydroperoxide in 3.75 parts of pure water, a reducing agent prepared by dissolving 0.012 parts of sodium D-arabinose ascorbate in 3.0 parts of pure water, and an emulsifier prepared by dissolving 0.5 parts of sodium alkyl diphenyl ether disulfonate in 3.8 parts of pure water were continuously and quantitatively pressed. During this time, the temperature of the mixture was maintained at 45° C. while stirring the contents, and the reaction was carried out until the internal pressure was sufficiently reduced.
[0183] The polymerization yield was 99.8%. Since the polymerization yield was almost 100%, the composition of the copolymer was roughly the same as the feed ratio. The particle size of the vinylidene chloride copolymer resin latex obtained in this way was 169nm. After removing the unreacted monomers from the obtained latex by steam stripping, the pH was adjusted to 3.0 using 12% sodium pyrophosphate, and the solid content was adjusted to 50-60% with pure water. Using an 18% aqueous solution of sodium dodecylbenzene sulfonate, 0.6 parts of sodium dodecylbenzene sulfonate were added relative to the resin solid content in the latex to prepare it.
[0184] (Example 2)
[0185] A halogen-based aqueous dispersion was prepared in the same manner as in Example 1 except that the 18% aqueous solution of sodium dodecylbenzenesulfonate was changed to a 18% aqueous solution of dialkyl sulfosuccinate salt.
[0186] (Example 3)
[0187] A halogen-based aqueous dispersion was prepared in the same manner as in Example 1 except that the 18% aqueous solution of sodium dodecylbenzenesulfonate was changed to an 18% aqueous solution prepared by mixing sodium alkylsulfonate and dialkylsulfosuccinate salt in a mass ratio of 79:29.
[0188] (Example 4)
[0189] A halogen-based aqueous dispersion was prepared in the same manner as in Example 1 except that the 18% aqueous sodium dodecylbenzenesulfonate solution was replaced with an 18% aqueous sodium palmitate solution.
[0190] (Reference Example 1)
[0191] A halogen-based aqueous dispersion was prepared in the same manner as in Example 1, except that the 18% aqueous solution of sodium dodecylbenzenesulfonate was replaced with an 18% aqueous solution of polyoxyethylene alkyl ether ammonium sulfate.
[0192] (Reference Example 2)
[0193] A halogen-based aqueous dispersion was prepared in the same manner as in Example 1 except that the 18% aqueous solution of sodium dodecylbenzenesulfonate was changed to the 18% aqueous solution of polyoxyalkylene decyl ether.
[0194] (Reference Example 3)
[0195] A halogen-based aqueous dispersion was prepared in the same manner as in Example 1, except that the 18% aqueous solution of sodium dodecylbenzenesulfonate was changed to an 18% aqueous solution of polyoxyalkylene decyl ether having a critical micelle concentration different from that of Reference Example 2.
[0196] (Reference Example 4)
[0197] A halogen-based aqueous dispersion was prepared in the same manner as in Example 1 except that the 18% aqueous solution of sodium dodecylbenzenesulfonate was changed to an 18% aqueous solution of polyoxyethylene oleyl ether.
[0198] (Comparative Example 1)
[0199] A halogen-based aqueous dispersion was prepared in the same manner as in Example 1 except that the 18% aqueous sodium dodecylbenzenesulfonate solution was changed to an 18% aqueous sodium alkylsulfonate solution.
[0200] (Comparative Example 2)
[0201] A halogen-based aqueous dispersion was prepared in the same manner as in Example 1 except that the 18% aqueous solution of sodium dodecylbenzenesulfonate was changed to the 18% aqueous solution of sodium alkyldiphenylether disulfonate.
[0202] (Example 5)
[0203] A halogen-based aqueous dispersion was prepared in the same manner as in Example 1 except that the amount of the added sodium dodecylbenzenesulfonate 18% aqueous solution was changed to 0.05 parts.
[0204] (Example 6)
[0205] A halogen-based aqueous dispersion was prepared in the same manner as in Example 1 except that the amount of the added sodium dodecylbenzenesulfonate 18% aqueous solution was changed to 0.3 parts.
[0206] (Example 7)
[0207] A halogen-based aqueous dispersion was prepared in the same manner as in Example 1 except that the amount of the added sodium dodecylbenzenesulfonate 18% aqueous solution was changed to 2.4 parts.
[0208] (Comparative Example 3)
[0209] A halogen-based aqueous dispersion was prepared in the same manner as in Example 1 except that the amount of the added sodium dodecylbenzenesulfonate 18% aqueous solution was changed to 2.5 parts.
[0210] (Reference Example 5)
[0211] A halogen-based aqueous dispersion was prepared in the same manner as in Example 1 except that the 18% aqueous solution of sodium dodecylbenzenesulfonate was changed to an 18% aqueous solution of polyoxyethylene oleyl ether and the blending amount was changed to 0.13 parts.
[0212] (Reference Example 6)
[0213] A halogen-based aqueous dispersion was prepared in the same manner as in Example 1 except that the 18% aqueous solution of sodium dodecylbenzenesulfonate was changed to a 18% aqueous solution of polyoxyethylene oleyl ether and the blending amount was changed to 0.3 parts.
[0214] (Reference Example 7)
[0215] A halogen-based aqueous dispersion was prepared in the same manner as in Example 1 except that the 18% aqueous solution of sodium dodecylbenzenesulfonate was changed to an 18% aqueous solution of polyoxyethylene oleyl ether and the blending amount was changed to 1.5 parts.
[0216] (Comparative Example 4)
[0217] A halogen-based aqueous dispersion was prepared in the same manner as in Example 1 except that the 18% aqueous solution of sodium dodecylbenzenesulfonate was changed to an 18% aqueous solution of polyoxyethylene oleyl ether and the blending amount was changed to 0.12 parts.
[0218] (Example 8)
[0219] A #4 Meyer bar was used on a 250 μm thick stretched polyvinyl chloride film subjected to corona discharge treatment so that the coating weight after drying was 2 g / m 2 The acrylic urethane anchor coating agent Emurdur 381A (manufactured by BASF) was applied as a primer, and dried in a hot air circulation dryer at 85°C for 15 seconds. The vinylidene chloride copolymer resin latex obtained in Example 1 was applied on the film using a Meyer rod so that the coating thickness after drying was 3 μm, and the drying conditions were dried in a hot air circulation dryer at 85°C with a wind speed of 4 m / s for 15 seconds.
[0220] (Example 9)
[0221] A test piece was prepared in the same manner as in Example 8 except that the coating was applied so that the coating thickness after drying would be 10 μm.
[0222] (Example 10)
[0223] A test piece was prepared in the same manner as in Example 8 except that the coating was repeatedly applied so that the coating thickness after drying would be 20 μm.
[0224] (Example 11)
[0225] A test piece was prepared in the same manner as in Example 8 except that the coating was repeatedly applied so that the coating thickness after drying would be 30 μm.
[0226] (Example 12)
[0227] A test piece was prepared in the same manner as in Example 8 except that the coating was repeatedly applied so that the coating thickness after drying would be 60 μm.
[0228] (Example 13)
[0229] A test piece was prepared in the same manner as in Example 8 except that the coating was repeatedly applied so that the coating thickness after drying would be 100 μm.
[0230] (Example 14)
[0231] A test piece was prepared in the same manner as in Example 8 except that the coating was applied so that the coating thickness after drying would be 1 μm.
[0232] (Comparative Example 5)
[0233] The film was a stretched polyvinyl chloride film of only 250 μm without coating with the vinylidene chloride copolymer resin latex.
[0234] (Example 15)
[0235] The same method as in Example 1 was used to prepare the product except that the polymerization was carried out so that VDC / MAN / MMA / AA=91.5 / 5.2 / 2.4 / 0.9.
[0236] (Example 16)
[0237] A test piece was prepared in the same manner as in Example 8 except that the coating was repeatedly applied so that the coating thickness after drying would be 70 μm.
[0238] (Example 17)
[0239] A test piece was prepared in the same manner as in Example 8 except that the coating was repeatedly applied so that the coating thickness after drying would be 90 μm.
[0240] (Example 18)
[0241] A test piece was prepared in the same manner as in Example 8 except that the coating was repeatedly applied so that the coating thickness after drying would be 120 μm.
[0242] (Example 19)
[0243] A test piece was prepared in the same manner as in Example 8 except that the coating was repeatedly applied so that the coating thickness after drying would be 150 μm.
[0244] (Example 20)
[0245] A test piece was prepared in the same manner as in Example 8 except that the coating was repeatedly applied so that the coating thickness after drying would be 180 μm.
[0246] (Example 21)
[0247] A vinyl chloride sheet coated with a vinylidene chloride copolymer produced by the same method as in Example 12 was left to stand in a constant temperature room at 40° C. and 50% RH for 7 hours to prepare a test piece.
[0248] (Example 22)
[0249] A vinyl chloride sheet coated with a vinylidene chloride copolymer produced by the same method as in Example 12 was left to stand in a constant temperature room at 40° C. and 50% RH for 14 hours to prepare a test piece.
[0250] (Example 23)
[0251] A vinyl chloride sheet coated with a vinylidene chloride copolymer produced by the same method as in Example 12 was left to stand in a constant temperature room at 40° C. and 50% RH for 17 hours to prepare a test piece.
[0252] (Example 24)
[0253] A vinyl chloride sheet coated with a vinylidene chloride copolymer produced by the same method as in Example 12 was left to stand in a constant temperature room at 40° C. and 50% RH for 26 hours to prepare a test piece.
[0254] (Example 25)
[0255] A test piece was prepared by the same method as in Example 12 except that the drying temperature was 95°C.
[0256] (Example 26)
[0257] A test piece was prepared by the same method as in Example 12 except that the drying temperature was 90°C.
[0258] (Example 27)
[0259] A test piece was prepared in the same manner as in Example 12 except that the drying time was set to 80°C.
[0260] The following evaluations were performed using the samples obtained in Examples, Reference Examples, and Comparative Examples. The results are shown in Tables 2 to 8.
[0261] (1) Foamability
[0262] A #4 Meyer bar was used on a 250 μm thick stretched polyvinyl chloride film subjected to corona discharge treatment so that the coating weight after drying was 2 g / m 2 The acrylic urethane anchor coating agent Emurdur 381A (manufactured by BASF) was applied as a primer, and dried in a hot air circulation dryer at 85°C for 15 seconds. The vinylidene chloride copolymer resin latex obtained in the examples, reference examples, and comparative examples was dried once with a Meyer rod to a coating weight of 10 to 15 g / m 2 The coating was applied on the film in a constant temperature and humidity chamber at 20°C and 55% RH, and dried at 60°C for 60 seconds at a wind speed of 6m / s using a hot air circulation device. The coating was repeated until the coating weight after drying was 80 to 100 g / m 2 until.
[0263] A metal tray was placed inside a vacuum dryer DP32 (manufactured by Yamato Scientific) regulated at 170°C, and the film was cut into 9 cm squares on the tray using scissors, left to stand and then heated for 3 minutes, and vacuum-heated at a vacuum degree of -9.3 kPa or more using a vacuum pump PX-51 (manufactured by Yamato Scientific) while maintaining 170°C. After vacuum heating, the film was taken out and judged by visual inspection. The film coated with Comparative Example 1 under the same conditions was used as a comparison, and the evaluation criteria were the following 4 grades.
[0264] ◎ (Excellent): No foaming was observed on the film surface with the naked eye in all samples.
[0265] ○ (slightly excellent): Some samples included samples in which foaming could be confirmed by naked eyes.
[0266] △ (good): In all samples, 2 When the number of bubbles on the film surface was measured, 1 to 150 bubbles were generated which could be confirmed with the naked eye, but there was no problem in practical use.
[0267] × (defective): In all samples, 2When the number of bubbles on the film surface was measured, 150 or more bubbles were generated that could be confirmed by the naked eye, which was not ideal for practical use.
[0268] (2) Coating properties
[0269] A #4 Meyer bar was used on a 250 μm thick stretched polyvinyl chloride film subjected to corona discharge treatment so that the coating weight after drying was 2 g / m 2 The acrylic urethane anchor coating agent Emurdur 381A (manufactured by BASF) was applied as a primer, and dried in a hot air circulation dryer at 85°C and 4 m / s for 15 seconds. The vinylidene chloride copolymer resin latex obtained in the examples, reference examples, and comparative examples was dried once with a Meyer rod to a coating weight of 10 to 15 g / m 2 The coating was applied on the film in the manner of , and dried in a constant temperature and humidity chamber at 20°C and 55% RH at 60°C for 60 seconds at a wind speed of 9 m / s using a hot air circulation device to prepare a coating film.
[0270] The above films were visually inspected for evaluation. The film of Comparative Example 1 coated under the same conditions was used as a comparison, and the evaluation criteria were the following 4 levels. The evaluation criteria for coating properties are shown in Figure 1 .
[0271] ◎(Excellent): The coating surface is uniform and completely free of defects
[0272] ○ (slightly excellent): The coated surface is substantially uniform, and a frame phenomenon can be slightly confirmed by visual observation.
[0273] △ (good): Rib-like defects can be visually confirmed on the coated surface, and a slight frame phenomenon can be visually confirmed, but there is no problem in practical use.
[0274] × (bad): Rib-like defects can be visually confirmed on the coated surface, and a frame phenomenon occurs significantly and can be visually observed, which is not ideal for practical use.
[0275] (3) Recoatability
[0276] A #4 Meyer bar was used on a 250 μm thick stretched polyvinyl chloride film subjected to corona discharge treatment so that the coating weight after drying was 2 g / m 2 The acrylic urethane anchor coating agent Emurdur 381A (manufactured by BASF) was applied as a primer, and dried in a hot air circulation dryer at 85°C for 15 seconds. The vinylidene chloride copolymer resin latex obtained in the examples, reference examples, and comparative examples was dried once with a Meyer rod to a coating weight of 10 to 15 g / m 2The coating was applied on the film in a constant temperature and humidity chamber at 20°C and 55% RH, and dried at 60°C for 60 seconds at a wind speed of 6m / s using a hot air circulation device. The coating was repeated until the coating weight after drying was 80 to 100 g / m 2 until.
[0277] The film was visually inspected and evaluated. The film of Comparative Example 1 coated under the same conditions was used as a comparison, and the evaluation criteria were the following 4 levels. The evaluation criteria for recoatability are shown in Figure 2 .
[0278] ◎(Excellent): The coating surface is uniform and completely free of defects
[0279] ○ (slightly excellent): The coating surface was slightly uneven.
[0280] △ (Good): Orange peel or ribbing occurs, and the transparency is poor, but there is no problem in practical use
[0281] × (bad): Orange peel or ribbing occurs, and the transparency is lacking, which is not ideal for practical use.
[0282] (4) Barrier properties
[0283] A #4 Meyer bar was used on a 250 μm thick stretched polyvinyl chloride film subjected to corona discharge treatment so that the coating weight after drying was 2 g / m 2 The acrylic urethane anchor coating agent Emurdur 381A (manufactured by BASF) was applied as a primer, and dried in a hot air circulation dryer at 85°C for 15 seconds. The vinylidene chloride copolymer resin latex obtained in the examples, reference examples, and comparative examples was dried using different types of Meyer rods so that the coating weight after one drying was 3 to 15 g / m 2 The coating was applied on the film in the manner of 400 g / m2. The drying conditions were as follows: the coating was applied at 85°C for 15 seconds at a wind speed of 4 m / s using a hot air drying cycle dryer. The coating was repeated until the coating weight after drying was 3 to 150 g / m2. 2 until.
[0284] As an evaluation of the barrier properties, the oxygen permeability of the film was measured. The coating film was fully humidified at room temperature and a relative humidity of 100%, and then the oxygen permeability was measured at 23°C and a relative humidity of 80% using OX-TRAN100 (manufactured by Modern Control).
[0285] In addition, as an evaluation of the barrier properties, the water vapor permeability of the film was measured. The coating film was fully humidified at room temperature and a relative humidity of 100%, and then the water vapor permeability was measured at 38°C and a relative humidity of 100% using PERMATRAN W3 / 31 (manufactured by Modern Control).
[0286] The coating film was cut using a large rotary microtome OSK 97LF506 (manufactured by OGAWA SEIKI) to prepare a slice, and the cross section of the slice was observed using a microscope KH-7700 (manufactured by HIROX) to measure the film thickness.
[0287] (5) Critical micelle concentration
[0288] The amphiphilic compound was dissolved in water at a concentration of 0.001 mass%, 0.005 mass%, 0.010 mass%, 0.015 mass%, 0.020 mass%, 0.025 mass%, 0.030 mass%, 0.035 mass%, 0.040 mass%, 0.045 mass%, 0.050 mass%, 0.055 mass%, 0.060 mass%, 0.065 mass%, 0.070 mass%, 0.075 mass%, 0.080 mass%, 0.085 mass%, 0.090 mass%, 0.095 mass%, and 0.1 mass% to prepare an aqueous solution, and the surface tension was measured by the Wilhelmy method. In the measurement of the surface tension, an automatic surface tensiometer CBVP-Z (manufactured by Kyowa Interface Chemical) was used to measure in a constant temperature room at 20°C and 55%RH. The obtained surface tension was plotted for each concentration (mass %). As the concentration increased from the low concentration side, the surface tension decreased, but the value became constant after a certain concentration. The concentration (mass %) at the inflection point was taken as the critical micelle concentration.
[0289] (6) Surface tension
[0290] The surface tension was measured by a plate method in a constant temperature room at 20°C and 55%RH using an automatic surface tensiometer CBVP-Z (manufactured by Kyowa Interface Chemical Co., Ltd.).
[0291] (7)Film thickness
[0292] The multilayer films obtained in Examples and Comparative Examples were cut using a microtome (RM2245 manufactured by LEICA) and observed using an electron microscope (TM4000plus manufactured by Hitachi) to measure the thickness of the dried coating film of the water dispersion layer.
[0293] (8) Moisture content
[0294] Using the measuring unit MKC-710M, the moisture vaporization device ADP-611, and the control unit MCU-710 manufactured by Kyoto Electronics Co., Ltd., the ADP-611 was purged with nitrogen at a flow rate of 200 ml / min for more than 30 minutes, and 0.1000 g ± 0.05 g of the multilayer film coated with the halogenated vinyl polymer was placed on the sample plate, purged at 180° C. for 3 minutes, and then measured at 160° C. The operation was repeated 3 times with the sample replaced, and the average value of the 3 times was taken as the moisture content.
[0295] (9) Relative crystallinity
[0296] The IR Affinity-1S manufactured by Shimadzu Corporation was used and the resolution was set to 4 cm -1 The coated surface of vinylidene chloride was irradiated with infrared rays and measured by the ATR method.
[0297] During crystallization, it is known that chlorine enhances the CC dipole moment due to configuration change, so 1046cm -1 Taking advantage of this, the 800cm -1 Up to 1320cm -1 Connected in a straight line, through 1046cm -1 (CC bond of polyvinylidene chloride) / 1070cm -1 The ratio of the peak heights (CH bonds of the polyvinylidene chloride skeleton) was determined and used as the relative crystallinity (CI value).
[0298]
[0299] [Table 3]
[0300]
[0301] [Table 4]
[0302]
[0303]
[0304] [Table 6]
[0305]
[0306] [Table 7]
[0307]
[0308] [Table 8]
[0309]
[0310] Industrial Applicability
[0311] The excellent vinylidene chloride latex prepared by the present invention does not impair the appearance even when thickly coated and has excellent water vapor and oxygen barrier properties, so it can be suitably used as a coating on various materials such as food or drug packaging films, paper, and general household products.
Claims
1. An aqueous dispersion of a halogenated vinyl polymer, characterized in that: The invention comprises a vinyl halide polymer including a structural unit derived from vinylidene chloride and an anionic amphiphilic compound having a hydrophilic index of 10.0 to 38.0 in an amount of 0.1% to 0.7% by mass based on the resin solid content.
2. The aqueous dispersion of a halogenated vinyl polymer as claimed in claim 1, comprising sodium pyrophosphate. 3 . The aqueous dispersion of a vinyl halide polymer according to claim 1 , comprising more than 0.12% by mass of a nonionic amphiphilic compound based on the solid content of the resin.
4. The aqueous dispersion of a vinyl halide polymer according to claim 1 or 2, wherein The vinyl halide polymer is contained in an amount of 30% by mass or more and 80% by mass or less in terms of solid content.
5. The aqueous dispersion of the vinyl halide polymer according to claim 1 or 2, wherein The mass ratio of the anionic amphiphilic compound is 0.05 mass % or more and 2.0 mass % or less relative to 100 mass % of the resin solid content contained in the water dispersion.
6. The aqueous dispersion of a vinyl halide polymer according to claim 1 or 2, wherein The anionic amphiphilic compound is selected from the group consisting of carboxylates, sulfates, sulfonates, phosphates, and gemini amphiphilic compounds.
7. The aqueous dispersion of a vinyl halide polymer according to claim 2, wherein The mass ratio of the sodium pyrophosphate is 0.05 mass % or more relative to 100 mass % of the resin solid content contained in the water dispersion.
8. A multilayer film, characterized in that The invention comprises a layer obtained by applying the aqueous dispersion of the vinyl halide polymer according to any one of claims 1 to 7 to a base film composed of a polymer different from the vinyl halide polymer.
9. The multilayer film of claim 8, having two or more layers coated with the aqueous dispersion of the halogenated vinyl polymer.
10. The multilayer film according to claim 8 or 9, wherein At least one of the layers coated with the aqueous dispersion of the halogenated vinyl polymer has a thickness of 1 μm or more.
11. The multilayer film according to claim 8 or 9, wherein At least one of the layers coated with the aqueous dispersion of the halogenated vinyl polymer has a thickness of 30 μm or more.
12. The multilayer film according to claim 8 or 9, wherein The water content is 1 mass % or less.
13. The multilayer film according to claim 8 or 9, wherein The layer coated with the aqueous dispersion of the halogenated vinyl polymer has a relative crystallinity of 1.1 or more as measured using a Fourier transform infrared spectrophotometer.
14. The multilayer film according to claim 8 or 9, wherein The thickness of the layer coated with the aqueous dispersion of the halogenated vinyl polymer is 200 μm or less.
15. A blister package for medicine, characterized in that: The multilayer film comprises the multilayer film according to any one of claims 8 to 14.
Citation Information
Patent Citations
JP1973058078A
Low-foaming vinylidene chloride-based latex
JP2000239468A
Synthesis method of hydroxylated polyvinyl chloride copolymer resin
CN102766231A
Polyvinylidene chloride copolymer emulsion for pharmaceutical packing coating and preparation method and application thereof
CN103059202A
Vinylidene chloride copolymer latex and film for blister pack
CN104114585A